LEMBAGA PERADILAN DALAM PERSPEKTIF PEMBARUAN HUKUM - Hoesein, Zainal Arifin (Jurnal Media Hukum, 2013)
The study aims at knowing the judicial power in legal reform perspective. In principle the rule of law, all public policy and election of public officials must be based on the rule of law. To realize the principle of supremacy of law, then one major factor is the presence of the judiciary is the embodiment of judicial power is independent, and authoritative. Law enforcement can not be regarded merely as a process of applying the law, however, has a broader dimension especially with regard to the dimensions of human behavior. The legal problems that will always stand out is the problem of "law in action" and not "law in the books". The judge is not only a spokesman for the law, but even further is the spokesman for law and justice. This means that the judiciary function as an institution that is able to translate the law in concrete when dealing with written legal norms/laws, and even be able to find the law, when a legal vacuum. In this perspective the judiciary can function as a locomotive of legal reform, if the judiciary can run freely and independently, and adhering to the principles of justice and expediency.Key words: Judiciary, Legal reform, and independent